Opportunities for early career members. Issue 2 (June 2017) - Bos, Lieuwe D.; Bartel, Sabine; Mathioudakis, Alexander G.; Flood, Emma
The Early Career Member Committee (ECMC) is always looking for young researchers (aged <40 years) who would like to get involved in the society. Join to let us know your interests: you can be asked to write a paper for Breathe, chair a session at the annual conference or submit a grant application for a fellowship. Read about upcoming opportunities for @ERStalk Early Career Members http://ow.ly/QFyb30b7iKq